Dance Education of "Asyeik" in the Ritual Procession of the Heirloom Bathing Ritual - Yedes Ratmi; Heldi Heldi; Budiwirman Budiwirman (International Journal of Educational Dynamics, 2022)
Asyeik dance at the ritual ceremony of bathing heirloom tools is believed by the community to be a sacred ceremony. This can be observed from the initial process of determining everything related to the time, place, performer, and pre-means of the ceremony. About the perpetrators, especially the dancers, the vibrations of sacred emotions are strongly felt when the shamans begin to chant verses. This study aims to explain the shape, function, and meaning of Asyeik dance, know the ceremonial procession of heirloom Bathing Rituals, and explain the durability and values of Asyeik dance in heirloom Bathing Rituals in Koto Baru Sub-district. This research instrument is the researcher himself and is assisted by supporting instruments such as stationery, recording devices, and cameras. Data collection techniques are carried out using literature studies, observations, interviews, and documentation. The steps of analyzing data are data reduction, data presentation, and concluding. The results of this study show that the ritual of bathing heirloom tools has long been carried out by the people of Koto Baru Sub-district, this tradition is still carried out today, and people still believe in the existence of the spirits of their ancestors, with this ritual as their link to other dimensions.